Xuebijing Ameliorates Sepsis-Induced Lung Injury by Downregulating HMGB1 and RAGE Expressions in Mice. (2nd March 2015) - Wang, Qiao; Wu, Xin; Tong, Xiaowen; Zhang, Zhiling; Xu, Bing; Zhou, Wugang
Abstract : Xuebijing (XBJ) injection, a traditional Chinese medicine, has been reported as a promising approach in the treatment of sepsis in China. However, its actual molecular mechanisms in sepsis-induced lung injury are yet unknown. Therefore, this study aimed to investigate the beneficial effects of XBJ on inflammation and the underlying mechanisms in a model of caecal ligation and puncture-(CLP-) induced lung injury. The mice were divided into CLP group, CLP+XBJ group (XBJ, 4 mL/kg per 12 hours), and sham group. The molecular and histological examinations were performed on the lung, serum, and bronchoalveolar lavage (BAL) fluid samples of mice at the points of 6, 24, and 48 hours after CLP. The results show that XBJ reduces morphological destruction and neutrophil infiltration in the alveolar space and lung wet/dry weight ratio, which improves mortality of CLP-induced lung injury. Meanwhile, XBJ treatment downregulates high mobility group box protein 1 (HMGB1) and the receptor for advanced glycation end products (RAGE) expression, as well as neutrophil counts, production of IL-1 β, IL-6, and TNF- α in the BAL fluids. In conclusion, these results indicate that XBJ may reduce the mortality through inhibiting proinflammatory cytokines secretion mediated by HMGB1/RAGE axis.